2011
DOI: 10.1007/978-3-642-23678-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of JPEG XR Compression Settings on Iris Recognition Systems

Abstract: Abstract. JPEG XR is considered as a lossy sample data compression scheme in the context of iris recognition techniques. It is shown that apart from low-bitrate scenarios, JPEG XR is competitive to the current standard JPEG2000 while exhibiting significantly lower computational demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A further example is the optimization of JPEG 2000 Part 2 wavelet packet decomposition structures with respect to optimizing iris [36] and fingerprint [37] recognition accuracy, which provided better results than rate-distortion optimized wavelet packet structures. Even JPEG XR was optimized for the iris recognition context [38].…”
Section: Biometricsmentioning
confidence: 99%
“…A further example is the optimization of JPEG 2000 Part 2 wavelet packet decomposition structures with respect to optimizing iris [36] and fingerprint [37] recognition accuracy, which provided better results than rate-distortion optimized wavelet packet structures. Even JPEG XR was optimized for the iris recognition context [38].…”
Section: Biometricsmentioning
confidence: 99%
“…Konrad et al [16] investigate tuning opportunities for JPEG and show, that by customizing quantization tables in JPEG, recognition performance can be increased. In [13] effects of JPEG-XR compression on iris recognition are examined. JPEG-XR is found to be competitive to the current standard JPEG 2000 while exhibiting significantly lower computational demands.…”
Section: Related Workmentioning
confidence: 99%
“…Due to its lower complexity compared to JPEG2000 we wanted to evaluate if there is also a difference in terms of face detection. In the work of Horvat, Stögner and Uhl, JPEG XR was analyzed on Iris Recognition Systems [7] and they concluded that JPEG XR performed better than JPEG2000.…”
Section: Jpeg Xrmentioning
confidence: 99%